Histidine 73 methylation coordinates β-actin plasticity in response to key environmental factors - Adrien Schahl; Louis Lagardère; Brandon Walker; Pengyu Ren; Hugo Wioland; Maya Ballet; Antoine Jégou; Matthieu Chavent; Jean-Philip Piquemal (Nature Communications)
Abstract The functional importance of the methylation of histidine 73 (H73) in actin remains unclear. Focusing on cytoplasmic β-actin, present in all mammalian cells, we use molecular dynamics simulations with a polarizable force field and adaptive sampling to examine the effects of H73 methylation. Our results show that methylation enhances nucleotide binding cleft opening, alters allosteric pathways connecting subdomains 2 and 4 (SD2 and SD4) in G-actin, and affects backdoor openings and inorganic phosphate release in F-actin, as validated by biochemical assays. These effects depend on the nucleotide and ions interacting with the actin. Together, our findings reveal how H73 methylation regulates β-actin plasticity and integrates environmental cues.